Kajian Kes Nama Orang Jawa di Surakarta: Dinamik dan Sistem - Widodo, Sahid Teguh (2010)
This qualitative research examined the Javanese' name system. Specifically, the study focused on two aspects of Javanese name systems, namely: the development of Javanese name formation and the language itself. The purpose of this study was to investigate the development of the formation of Javanese' names and its linguistic pattern relevant to its contexts. This study is a case study of Javanese name formation and linguistic pattern in Surakarta. Multiple research techniques and various types of data base (i.e. documents, archives, spoken, written) were collected to study the phenomenon under investigation. This study also applied grounded theory approach, which inductively studies represented phenomena, located in Surakarta City, Central Java, Indonesia. This research concludes that the Javanese naming tradition in Surakarta is related to dynamic process of its society. Uniquely, names in Surakarta evidently, become a way of expressing specific 'world' condition relative to the society and culture in Surakarta. These include goals, ideas, and feelings. Javanese names historically shows developmental changes, shifts, and adaptive changes toward varieties of forms of social and natural phenomena. The richness of the data suggested that Javanese names are related to their contexts, i.e. varieties of dynamic, social and cultural phenomena. In addition, the formation of Javanese names in Surakarta could be categorized into five phases of development. These include: (1) Hindu and Buddha phase, (2) Hindu Javanese phase - the influences of Hindu to Javanese names, (3) Islamic Javanese phase - the influence of Islam on Javanese names which could be classified into two sub-phases: Demak Kingdom and Pajang and Mataram Islam Kingdom phase, (4) Modem phase - modem names due to modernization and social changes, and (5) Contemporary phase - the existence of complex, freedom and lifestyles. The historical views of Javanese names exhibited that names are related to contexts. Last but not least, the linguistic perspective suggested six findings in relation to Javanese's name system. These include: (1) the structure of Javanese names, (2) components of Javanese names, (3) elements of Javanese names, (4) sex markers of Javanese names, (5) Javanese paraban names, and (6) meaning of Javanese names. Based on the six findings it can be concluded that Javanese's name system is a unique sub-system of linguistic construct and is different from linguistic system in general.